Knee joint endoprosthesis loading in full extension - Zach, Lukas; Konvickova, Svatava; Ruzicka, Pavel; Cheze, Laurence (Annual International Conference of the IEEE Engineering in Medicine and Biology Society. IEEE Engineering in Medicine and Biology Society. Annual International Conference, 2007)
This paper deals with a knee joint endoprosthesis finite element analysis. Based on a three dimensional geometric model of a lower extremity, a mechanical axis of the limb was designed. This axis is important for several reasons. Firstly, the endoprosthesis was positioned due to its direction, secondly, boundary conditions was defined on its proximal and distal end and finally, the axis enabled reasonable simplification of the model which led to the time saving analysis while preserving principal features of the model like the natural boundary conditions or knee joint's degrees of freedom . Having this, one leg stance was simulated. Results of the analysis were encouraging for future models. Especially the choice of the mechanical axis was suitable and enabled a better distribution of contact pressures and stress on both femoral and tibial component compared to our former models. Also their magnitudes correspond better the manufacturer's experience and our findings. The stresses did not exceeded 30MPa for the UHMWPE tibial plateau and 100MPa for the femoral component. The contact pressures were lower than 40MPa.
Keywords: Stress, Mechanical; Knee Prosthesis; protézy kolene; Humans; Models, Biological; Range of Motion, Articular; Pressure; Femur; mechanický stres; Weight-Bearing; kolenní kloub; biologické modely; femur; Knee Joint; rozsah kloubních pohybů; tibie; zatížení muskuloskeletálního systému; lidé; tlak; Tibia